Interaction between spawning habitat and coastally steered circulation regulate larval fish retention in a large shallow temperate bay. (20th December 2015) - Álvarez, Itziar; Catalán, Ignacio A.; Jordi, Antoni; Alemany, Francisco; Basterretxea, Gotzon
Abstract: Larval retention plays a fundamental role in the persistence of coastal fish assemblages. Here, we examine larval fish distribution and abundance patterns in Palma Bay, a large (∼20 km) wind-driven microtidal bay in the southern coast of Mallorca (Spain, NW Mediterranean Sea). Larval fish assemblage structure in the bay were analyzed during July 2010 and interpreted in the context of the observed circulation patterns, adult habitat distribution and spawning traits. Acoustic Doppler Current Profiler (ADCP) observations showed the presence of retentive flow patterns in the middle of the bay enhancing local larval accumulation and self-recruitment. In consequence, larval abundances were higher in this central part of the bay (∼40 m depth, mean abundance 607.6 ± 383 ind. 10 m −2 ) than along the coastal fringe (<35 m 113.7 ± 91 ind. 10 m −2 ). Also, a multivariate predictive approach based on Redundancy Analysis (RDA) revealed differences between the larval fish assemblages in areas inside the bay, constituted by small pelagic and benthopelagic taxa (gobids, Chromis chromis and Serranus hepatus ) and offshore larvae, mostly from meso and large pelagic fish. These larval fish assemblages were structured according to depth variations and zooplankton abundance, and remained relatively unmixed because of the circulation patterns in the mouth of the bay that uncouple its dynamics from alongshelf circulation. Even larvae of typically pelagic species that spawn close to the coast ( Sardinella aurita, Auxis rochei ) were associated with the retentive effect of the bay. Our study highlights the important role of coastal bays in the regulation of coastal fish population dynamics and as hotspots for the maintenance of diversity in the Mediterranean Sea.